Bentuk Sapaan sebagai Cermin Struktur Sosial Orang Jawa: Analisis Antropolinguistik - Khairunnazwa Salsabila; Nursukma Suri (Yayasan Al-Afif, 2025)
This study discusses forms of address in Javanese society as a reflection of social structure through an anthropolinguistic approach. Addresses are viewed not only as linguistic elements, but also as cultural practices that reflect social relations based on age, status, position, and level of familiarity. This study aims to describe the types of address used by Javanese society, analyze the relationship between address selection and socio-cultural values such as polite language, and explain the dynamics of changes in address amidst modernization. The research method uses a qualitative approach with descriptive analysis techniques through literature studies and social context analysis. The results show that traditional address forms such as mas, mbak, pak, bu, and kinship terms still function in maintaining social harmony, while the younger generation shows a tendency to use neutral and modern address forms such as kamu, aku, bro, and sis. The conclusion of the study reveals that address forms are a representation of cultural values as well as indicators of social change in Javanese society.